After the End of Art : Contemporary Art and the Pale of History - Updated Edition - Danto, Arthur Coleman (Book collections on Project MUSE., 2014)
"Originally delivered as the prestigious A.W. Mellon Lectures in the Fine Arts in 1995, After the End of Art remains a classic of art criticism and philosophy, and continues to generate heated debate for contending that art ended in the 1960s. Arthur Danto, one of the best-known art critics of his time, presents radical insights into art's irrevocable deviation from its previous course and the decline of traditional aesthetics. He demonstrates the necessity for a new type of criticism in the face of contemporary art's wide-open possibilities"--Page 4 of cover.